2018
DOI: 10.1111/jfbc.12529
|View full text |Cite
|
Sign up to set email alerts
|

Bone health-promoting bioactive peptides

Abstract: Bioactive peptides, derivatives of proteins, show versatile biological effects and represent potential health-promoting agents as functional food ingredients and/or nutraceuticals. Bone health depends on the balance between bone formation and resorption. When the balance is disrupted, bone diseases such as osteoporosis and fragility fractures may result. Accumulating evidence suggests that peptides derived from endogenous proteins and food proteins enhance bone health.This article reviews the literature on pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Peptides have gained significant interest in recent years due to their various beneficial effects on human health [ 14 , 25 ]. Enzymatic hydrolysis is an important approach for the production of functional peptides from a variety of food proteins [ 7 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Peptides have gained significant interest in recent years due to their various beneficial effects on human health [ 14 , 25 ]. Enzymatic hydrolysis is an important approach for the production of functional peptides from a variety of food proteins [ 7 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that FMPs promoted proliferation and calcium deposition in osteoblastic MC3T3‐E1 cells but not in skim milk‐supplemented cells (data not shown). Fermented milk‐derived peptides, such as casein phosphopeptides, promote vitamin D‐dependent bone calcification, which is beneficial for bone health (Ahn and Je 2019). Dietary lactic acid may also increase bone formation by increasing calcium and phosphorus absorption (Chonan et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…[Colour figure can be viewed at wileyonlinelibrary.com] milk-derived peptides, such as casein phosphopeptides, promote vitamin D-dependent bone calcification, which is beneficial for bone health (Ahn and Je 2019). Dietary lactic acid may also increase bone formation by increasing calcium and phosphorus absorption (Chonan et al 1998).…”
Section: Mrna Expression Levels Of Bone Remodelling and Inflammatory mentioning
confidence: 99%
“…BAPs can be obtained by proteolytic cleavage with specific proteases and identified as promising nutraceuticals or pharmaceuticals [ 20 ]. In addition, studies show that BAPs can regulate MSC differentiation into osteoblasts by activating specific signaling pathways, such as Wnt signaling [ 21 , 22 , 23 , 24 ]. Recently, our group developed BAPs that can regulate MSC differentiation into osteoblasts and adipocytes [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%